2021
DOI: 10.1016/j.ctro.2021.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Limited-stage small cell lung cancer: Outcomes associated with prophylactic cranial irradiation over a 20-year period at the Princess Margaret Cancer Centre

Abstract: Background & purpose: Prophylactic cranial irradiation (PCI) is recommended for limited-stage small-cell lung cancer (LS-SCLC) patients with good response to concurrent chemoradiation. We report our institution's 20-year experience with this patient population and associated clinical outcomes. Materials & methods: A retrospective cohort of consecutive LS-SCLC patients treated with curative intent chemoradiation at our institution was reviewed. Overall survival (OS) was calculated using the Kaplan-Meier method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Though with some controversy after the publication of Takahashi’s study ( 10 15 ), PCI is still recommended in many guidelines ( 16 18 ). However, the application of PCI is not consistently accepted by doctors or patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though with some controversy after the publication of Takahashi’s study ( 10 15 ), PCI is still recommended in many guidelines ( 16 18 ). However, the application of PCI is not consistently accepted by doctors or patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of PCI is not consistently accepted by doctors or patients. Only about 70% of patients with LS-SCLC received PCI in M. D. Cancer center ( 13 ) and in the Princess Margaret Cancer Centre ( 10 ), and 57% of the patients with CR or PR response after chemoradiotherapy received PCI in Nakamura’s report form Japan ( 14 ). In the present study, only 52.4% of the patients received PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Michael Yan et al reported the outcomes of PCI for LS-SCLC over a 20-year period at the Princess Margaret Cancer Centre. The findings showed that PCI contributed to improved OS and lower BM risk (HR 1.88, 95% CI 1.32–2.69; HR 4.66, 95% CI 2.58–8.40, respectively) [ 21 ]. Conversely, in a recent analysis of 297 patients with LS-SCLC, PCI was not independently associated with substantial improvement in OS (HR 0.844, 95% CI 0.604–1.180, p = 0.32) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study at the Princess Margaret Cancer Centre showed improvements in OS and brain failure free survival for those that received PCI, however they observed some patients declined PCI due to patient or physician concerns related to toxicity and also patients older than 65 years of age were significantly less likely to receive PCI [23]. An updated study from the same institution showed PCI maintained its association with OS, even in the MRI era [24]. Another study from Memorial Sloan Kettering Cancer Center showed that patient concerns regarding neurotoxicity was the most cited reason for the omission of PCI.…”
Section: The Role Of Prophylactic Cranial Irradiationmentioning
confidence: 99%
“…Given the associated side effects with PCI, its utility to manage LS-SCLC patients when MRI brain surveillance is available is being questioned. In addition to the retrospective studies highlighted above, some studies have shown no associated improvement in OS or PFS with PCI for LS-SCLC in the MRI era [19,26] while other studies do report an OS benefit with PCI [24,27]. Further prospective results from clinical trials that include LS-SCLC patients, such as the SWOG S1827 MAVERICK (SWOG S1827) trial comparing PCI to MR surveillance (NCT04155034), are awaited to provide modern prospective evidence.…”
Section: The Role Of Prophylactic Cranial Irradiationmentioning
confidence: 99%